2005
DOI: 10.1002/pca.828
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase extraction and HPLC-MS profiling of pyrrolizidine alkaloids and theirN-oxides: a case study ofEchium plantagineum

Abstract: Pyrrolizidine alkaloids and their N-oxides can be extracted from the dried methanolic extracts of plant material using dilute aqueous acid. The subsequent integration of solid-phase extraction (with a strong cation exchanger) of the alkaloids and N-oxides from the aqueous acid solution, together with analysis using HPLC-ESI/MS, provides a method for the simultaneous profiling of the pyrrolizidine alkaloids and their N-oxides in plant samples and the collection of useful structural data as an aid in their ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(143 citation statements)
references
References 16 publications
8
135
0
Order By: Relevance
“…Several saturated and 1,2-unsaturated PAs (mainly as N-oxides) were detected using HPLC-ESI-MS in fresh pollen collected from flowers of the PAs producing plants Echium vulgare and E. plantagineum and /or from bee pollen from bees that had foraged on PA plants [12]. The same method has also been used to determine the PA profile in E. plantagineum [93], Cryptantha crassipes [64], and Anchusa strigosa [50]. PAs (N-oxides and free bases) occurring in small amounts could be efficiently analyzed using an RP-HPLC ion trap MS method with an atmospheric pressure chemical ionization (APCA) interface [167].…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several saturated and 1,2-unsaturated PAs (mainly as N-oxides) were detected using HPLC-ESI-MS in fresh pollen collected from flowers of the PAs producing plants Echium vulgare and E. plantagineum and /or from bee pollen from bees that had foraged on PA plants [12]. The same method has also been used to determine the PA profile in E. plantagineum [93], Cryptantha crassipes [64], and Anchusa strigosa [50]. PAs (N-oxides and free bases) occurring in small amounts could be efficiently analyzed using an RP-HPLC ion trap MS method with an atmospheric pressure chemical ionization (APCA) interface [167].…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 99%
“…For analytical purposes high-resolution capillary GLC alone or in combination with mass spectrometry is the method of choice for free PA bases [40,59,67,70,90,91,96,163,[191][192][193][194][195]. HPLC and HPLC-MS are also helpful but less sensitive than GLC and GLC-MS [60,93,[196][197][198][199]. In addition, the resolution is much lower than for GLC but in HPLC also PA-N-Oxides can be directly analysed.…”
Section: Phytochemical Analysis Of Pasmentioning
confidence: 99%
“…It is difficult to distinguish whether the effects of oil supplementation in methane mitigation are due to secondary metabolites, a particular fatty acid, or mixtures of fatty acids. Secondary compounds, like the pyrrolizidine alkaloids echimidine and echiumine, known to contribute to liver damage and photosensitivity in grazing livestock (Weston et al, 2013), are found in greatest quantity in E. plantagineum (Colegate et al, 2005). There are marked differences in the sensitivity of domestic species to echium toxicosis, with cattle and horses showing the highest levels of sensitivity (Cheeke, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation (10 min at 5,000g), zinc dust was added in excess to the supernatants, which were then stirred for 3 h for the complete reduction of alkaloid N-oxides. As SCX-SPE purification has been shown to be suitable for the enrichment of PAs (Colegate et al, 2005), the samples were further centrifuged (10 min at 5,000g) and then applied to SCX-SPE cartridges (Phenomenex) equilibrated with 6 mL of methanol and 6 mL of 0.05 M H 2 SO 4 . After each column had been washed with 12 mL of water and 12 mL of methanol, the alkaloids were eluted by applying 3 3 6 mL of methanol containing 5% (v/v) NH 4 OH.…”
Section: Radioactive Tracer Feeding Experiments and Product Analysismentioning
confidence: 99%